Immune Dysregulation and Cellular Composition in Lichen Sclerosus Revealed by Integrative Epigenetic Analysis with Cell Type Deconvolution - Wang J; Fan H; Bao Z; Li G; Wang L; Zhang D (Journal of Inflammation Research)
Jianwei Wang,1,* Hailang Fan,2,* Zhengqing Bao,1 Guizhong Li,1 Lingyan Wang,1 Dake Zhang2 1Urology Department, Beijing Jishuitan Hospital, Capital Medical University, Beijing, 102200, People’s Republic of China; 2Key Laboratory of Biomechanics and Mechanobiology, Ministry of Education; Key Laboratory of Innovation and Transformation of Advanced Medical Devices, Ministry of Industry and Information Technology; National Medical Innovation Platform for Industry-Education Integration in Advanced Medical Devices (Interdiscipline of Medicine and Engineering); School of Engineering Medicine, Beihang University, Beijing, 100191, People’s Republic of China*these authors contributed equally to the workCorrespondence: Lingyan Wang, Urology Department, Beijing Jishuitan Hospital, Capital Medical University, Beijing, People’s Republic of China, Email wang_lingyan@foxmail.com Dake Zhang, Key Laboratory of Biomechanics and Mechanobiology, Ministry of Education, Beijing Advanced Innovation Center for Biomedical Engineering, School of Engineering Medicine, Beihang University, Beijing, People’s Republic of China, Email dakezhang@buaa.edu.cnBackground: Lichen sclerosus (LS) is a chronic inflammatory disease affecting skin and mucosal tissues, particularly external genitalia, with a risk of cancer. Its etiology is unknown, possibly involving immune dysregulation and inflammation.Methods: Study used DNA methylation (DNAme) and single-cell RNA sequencing (scRNA-seq) to compare LS with normal skin. A detailed DNAme profile of LS was created, analyzing differentially methylated probes (DMPs) and cell type-specific DMPs. EpiSCORE deconvolution and immune infiltration analyses identified altered cell types in LS. Immunohistochemistry confirmed cellular changes. Enrichment analysis identified significantly altered pathways, and cell communication analysis described interactions among altered cell types in LS.Results: DNA methylation patterns generally distinguished LS from normal skin, with a few exceptions. Data analysis showed that T cells significantly increased and fibroblasts decreased in LS. Immunohistochemical staining confirmed the changes in T cells. Enrichment analysis of DMPs indicated significant impacts on fibroblast-related processes and key immune pathways. The COLLAGEN signal was the most prominent in the cell communication. The CD99-CD99 interaction was the strongest between T cells and fibroblasts.Conclusion: Combining DNAme and scRNA-seq data revealed changes in cellular composition and immune pathways in LS, enhancing understanding of its pathogenesis and highlighting potential therapeutic targets and diagnostic markers.Keywords: lichen sclerosus, DNA methylation, immune, T cells